The Effects of K+ Channel Blockade on Eccentric and Isotonic Twitch and Fatiguing Contractions in situ - Moyer, Michelle; van Lunteren, Erik (Frontiers in Physiology, 2012)
K+ channel blockers like 3,4-diaminopyridine (DAP) can double isometric muscle force. Functional movements require more complex concentric and eccentric contractions, however the effects of K+ channel blockade on these types of contractions in situ are unknown. Extensor digitorum longus (EDL) muscles were stimulated in situ with and without DAP in anesthetized rats and fatigability was addressed using a series of either concentric or eccentric contractions. During isotonic protocols (5-100% load), DAP significantly shifted shortening- and maximum shortening velocity-load curves upward and to the right and increased power and work. Maximum shortening, maximum shortening velocity and power doubled while work increased by approximately 250% during isotonic contraction at 50% load. During isotonic fatigue, DAP significantly augmented maximum shortening, work, shortening velocity and power. During constant velocity eccentric protocols (2-12 mm/s), DAP increased muscle force during eccentric contractions at 6, 8, 10 and 12 mm/s. During eccentric contraction at a constant velocity of 6mm/s while varying the stimulation frequency, DAP significantly increased muscle force during 20, 40 and 70 Hz . The effects of DAP on muscle contractile performance during eccentric fatigue varied with level of fatigue. DAP-induced contractile increases during isotonic contractions were similar to those produced during previously studied isometric contractions, while the DAP effect during eccentric contractions was more modest. These findings are especially important in attempting to optimize functional electrical stimulation parameters for spinal cord injury patients while also preventing rapid fatigue of those muscles.